On Syllable Weight in Amharic - Voigt, Rainer (Aethiopica, 2019)
Contrary to the claim made in a recently published article, that literature on Amharic stress is ‘almost nonexistent’, I present and quote from the works of Armbruster, Guidi, Abraham, and others, and discuss their concept of stress patterns in Amharic. However, my criticism mainly concerns the data base used in the aforementioned article which addresses the topic of syllable weight, and where an attempt is made to analyse stress in Amharic based on a large number of examples. In these examples, however, consonantal lengthening and the distinction between the central vowels ǝ and ä and ä and a are incorrectly represented in almost all verbal forms, infinitives, and adjectives. This is partly the result of the informants speaking Amharic as their second language, and partly due to the fieldworkers’ incomplete knowledge of the language. This gives rise to many mistakes even amongst the simplest one- and two-syllable words. Ultimately this raises the question of whether those authors’ linguistic conclusions on the moraic nature of codas can be regarded as safe since it is based on inaccurate data. I also apply my own analysis to Amharic reduplicated adjectival forms, which differs from the one proposed in the said article.